Integer Programming for Scheduling Computation Alternative Machines Parallel Multi Operations - Irwan Sukendar; S Suprayogi; Imam Much Ibnu Subroto (Journal of Telematics and Informatics, 2018)
This paper deals with integer programming for computing alternative scheduling problems of multi-parallel machine operation. The purpose function used is weighted total tardiness. The model formulation comprises the formulation of the objective function and the formulation of the 16 limiting functions. The model was tested using a numerical example consisting of four multi-operation jobs and several machine alternatives in mathematical software Lingo 9. The programming results show that a feasible solution with a weighted total tardiness measure size of eight.